Organizational climate and quality of work-life in the creativity of teachers - Masduki Ahmad; Suryadi Suryadi; Matin Matin; Sugiarto Sugiarto (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study analyzed the effect of organizational climate and quality of work-life on teachers’ creativity throughout state vocational high schools in Serang, Indonesia during the COVID-19 pandemic. This work involved 164 civil servant teachers in state vocational high schools in Serang, Indonesia as the sample. As the major analysis tool, we used a multiple linear regression model. The hypothesis test used the t-test and f-test. The study revealed that: i) Organizational climate positively and significantly influenced the civil servant teachers’ creativity amid the COVID-19 pandemic with a significance value of .000 (α<.005); ii) The quality of work-life also had a positive and significant effect on the teachers’ creativity during this difficult situation has significance value of .000 (α<.005); and iii) The quality of their work influenced both organizational climate and the creativity of state vocational high school teachers living in Serang, Indonesia, with a determination coefficient of .861 or 86.1% during the pandemic.